2016
DOI: 10.1038/srep24190
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of unintentional extra carriers by Mn valence change for high insulating devices

Abstract: For intrinsic oxide semiconductors, oxygen vacancies served as the electron donors have long been, and inevitably still are, attributed as the primary cause of conductivity, making oxide semiconductors seem hard to act as high insulating materials. Meanwhile, the presence of oxygen vacancies often leads to a persistent photoconductivity phenomenon which is not conducive to the practical use in the fast photoelectric response devices. Herein, we propose a possible way to reduce the influence of oxygen vacancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…The responsivity of 96.13 A W −1 was achieved under 5 V bias, which is reported to be the highest on a thin-film-based gallium oxide photodetector, demonstrating the good reliability to grow these photodetectors on an inexpensive Si substrate. 3,4,29,[35][36][37]44,45 Furthermore, the responsivity with the HSL-grown β-Ga 2 O 3 thin film photodetector has a rejection ratio more than 2 orders for 250 nm vs 400 nm, indicating its excellent solar-blind nature. Figure 4(b) shows the variation of the EQE with wavelength under various bias voltages, which is another important factor to determine the performance of a photodetector and is given by where R, h, c, e, and λ are the responsivity, Planck's constant, speed of light, electron charge, and wavelength of incident optical light, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The responsivity of 96.13 A W −1 was achieved under 5 V bias, which is reported to be the highest on a thin-film-based gallium oxide photodetector, demonstrating the good reliability to grow these photodetectors on an inexpensive Si substrate. 3,4,29,[35][36][37]44,45 Furthermore, the responsivity with the HSL-grown β-Ga 2 O 3 thin film photodetector has a rejection ratio more than 2 orders for 250 nm vs 400 nm, indicating its excellent solar-blind nature. Figure 4(b) shows the variation of the EQE with wavelength under various bias voltages, which is another important factor to determine the performance of a photodetector and is given by where R, h, c, e, and λ are the responsivity, Planck's constant, speed of light, electron charge, and wavelength of incident optical light, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In particular, for a thin-film-based planar photodetector a record-high responsivity and EQE are observed, which is even considerably higher than that of a solarblind β-Ga 2 O 3 photodetector fabricated on very expensive substrates. 4,24,29,[35][36][37]44,45,51 To determine the response rate and further explore the feasibility of the photodetector for practical applications as a solarblind photodetector, the real-time photocurrent transient response is studied by periodically switching a 254 nm optical signal on and off in self-power mode, without applying external power to the photodetector. For the β-Ga 2 O 3 thin film photodetector grown without HSL, the current increases to a non-stable value, and after switching off the optical signal the current does not reach its original value; rather, both the photocurrent and dark current consistently increase after repeated exposure, as shown in Figure 5(a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is generally thought that significant p-type conductivity can not be achieved reliably in β-Ga 2 O 3 , due to i) no shallow acceptor dopants being available [77,78], ii) the likely formation of self-trapped holes [60,61] and iii) self-compensation [77]. There is, however, a number of deep acceptors, such as Fe [5,71,141], Mn [142], Mg [67,76,91,143], Al [76], Co [76], Ni [76] and N [143] which are used to produce semi-insulating β-Ga 2 O 3 needed, for example, as a base for β-Ga 2 O 3 -based power electronics (see Fig. 4.1).…”
Section: Influence Of Defects On the Electrical Propertiesmentioning
confidence: 99%
“…This reduced PPC effect led to a fast recovery in the device from hours to <9 s upon turning off the incident light. 94 The PPC effect in Ga 2 O 3 PDs can be effectively suppressed by annealing in oxygen 110 or by doping divalent elements such as Zn and Mg. 111–114 Guo et al 115 reported that an SB photodetector based on β-Ga 2 O 3 exhibited a lower dark current and a faster response speed by Zn doping due to the reduction in the concentration of oxygen vacancies. Further, the band gap can be tuned continuously by alloying with different concentration ratios of Zn and Mg elements, which can remain unchanged with an appropriate ratio.…”
Section: Ga2o3 Materialsmentioning
confidence: 99%